A farewell to arms [videorecording (DVD)] - Borzage, Frank; Cooper, Gary, 1901-1961; Hayes, Helen, 1900-1993; Menjou, Adolphe, 1890-1963; LaRue, Jack; Hemingway, Ernest, 1899-1961 (Hollywood's leading men., 2004)
A wounded American soldier falls in love with his beautiful English nurse during World War I.